ANALYSIS OF INSECURITY, LABOUR FORCE, CAPITAL STOCK AND ECONOMIC GROWTH NEXUS IN NIGERIA - ABDULLAHI, NAZIRU YUSUF; BALA, ADAMU MARYAM (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study examines the interrelationship between insecurity, the labour force, capital stock, and economic growth in Nigeria, a nation facing complex socio-economic challenges. The primary objective is to analyze how these factors interact and influence economic growth. The study employs an Autoregressive Distributed Lag (ARDL) model to examine the relationship between the variables, after confirming their order of integration through an ex-ante analysis, which shows a mix of I(1) and I(0) processes. The ARDL model bound test confirms cointegration among the variables at the 1% significance level, suggesting that the Nigerian economy can recover from short-term shocks and reach equilibrium over time. The findings reveal that, in the short run, insecurity and capital stock do not significantly impact economic growth, while labour force participation has a positive and statistically significant influence. The speed of adjustment is slow, with a negative and significant coefficient of -0.038908, indicating the need for more immediate policy interventions to facilitate a quicker return to equilibrium. Key recommendations based on these findings include prioritizing national security and increasing labour force participation, particularly among youth, women, and rural populations, through education and skill development programs. However, the government should implement policies to enhance capital stock by improving infrastructure, fostering foreign direct investment (FDI), and enhancing access to affordable credit for small and medium-sized enterprises (SMEs). These actions will stimulate private sector growth and contribute to long-term economic development.